Rabies Titer Monitoring and Disease Surveillance - Barksdale, Allyson (My University, 2025)
Rabies is a dangerous disease of importance to public health. Its high case-fatality rate, zoonotic status, and the inability to treat it after symptoms have emerged make it a dangerous disease, but its economic burden makes it a disease of concern across many countries. Globally, dogs are the most common vector of rabies virus, but bats, skunks, and raccoons are the most common vectors of human exposure in the United States. Bats are the focus of this Applied Practical Experience due to their abundance, proximity to human dwellings, and their ability to infect via bite without notice. This APE involved learning Next Generation Sequencing to detect viral ribonucleic acid (RNA) viruses in bat samples. The future goal of this would be to collect samples from bats that were involved in human exposure cases but tested negative for rabies. Surveillance testing these bats would determine if other common bat diseases are on the rise and is important to maintain proper protocol for human safety. Most bats are brought in for rabies testing and are disposed of afterward. The results of a surveillance study would be useful to determine if this is still the common protocol, or if bats with human exposure should require other diagnostic tests for diseases after rabies testing is completed. The second goal of the APE involved learning the entire process of the titer monitoring side of rabies laboratory work. Guidelines are produced to keep laboratory workers protected when working with infectious pathogens and multiple sections and systems are needed for this to be effective. I worked with Quality Control, our Medical Records Coordinator, and Dr. Seetahal in her capacity as the Rabies Laboratory director, and this culminated in creating a Standard Operating Procedure (SOP) for rabies titer monitoring among the employees of the KSU Rabies Laboratory and the KSU College of Veterinary Medicine and a titer monitoring spreadsheet for tracking going forward.
Keywords: rabies; titer monitoring; laboratory safety; disease surveillance; bats